Valuation of proved vs. probable oil and gas reserves - Bård Misund; Petter Osmundsen (Cogent Economics & Finance, 2017)
Oil and gas reserves are the most important assets of oil and gas companies. A source of confusion for investors in oil companies, is that reserves quantities and values are uncertain estimates. Reserves are typically classified according to probabilities of recovery from underground reservoirs. All US-listed companies are required to disclose proved reserves but not probable reserves, thus leaving out potentially important information for investors and financial analysts. This study addresses the impact on market valuation of various classifications of reserves amounts. Using a data sample of 94 companies that do disclose information on probable reserves, we compare the relation between three classifications of reserves and oil company returns. While we find that information on probable reserves do not have an impact on stock returns measured over the entire time period, this is not the case since 2009, coinciding with the onset of the shale gas revolution.
Keywords: 330; oil and gas reserves; proved reserves; probable reserves; value relevance; oil company valuation; stock returns; valuation; Shell; Exxon; Chevron